From Domination to Negotiation: A Transformative Face Negotiation Framework for Government–Community Communication in North Lombok’s 3T Regions - Putra, Sandi Justitia; Hastjarjo, Sri; Rahmanto, Andre Noevi; Hermawati, Tanti (Jurnal Audiens, 2026)
This study examines the transformation of government–community communication in 3T regions, focusing on North Lombok Regency, through the lens of Face Negotiation Theory. It aims to explain how communication shifts from domination toward negotiation within structurally constrained and culturally embedded contexts. Drawing on an interpretive qualitative approach, the study employs in-depth interviews, participant observation, and document analysis to capture interactional dynamics in public communication forums. The findings reveal that communication remains largely dominated by top-down practices that generate systemic face threat and limit meaningful participation. However, situational facework—manifested through local mediators, culturally resonant language, and informal interaction spaces—emerges as an adaptive mechanism that reduces relational tension and enables limited dialogue. Despite these developments, negotiation remains predominantly procedural rather than substantive, as public input rarely influences decision-making outcomes. Consequently, communication transformation occurs in a gradual, partial, and contested manner. The study contributes by extending Face Negotiation Theory, developed by Stella Ting-Toomey, into the institutional domain through a Transformative Face Negotiation Framework, which integrates relational, cultural, and structural dimensions of communication. This framework highlights communication as a dynamic process shaped by the interplay between domination, adaptation, and constrained negotiation, offering a nuanced understanding of governance communication in marginalized contexts.